English as Students’ Major Problem in Tourism Classroom - Taufiq Kurniawan; Siti Danti; Lala Nining Indrawati (Universitas 45 Surabaya, 2023)
This study aims to examine the impact of using English as the language of instruction on the effectiveness of teaching and learning in non-English majors in tourism classes, its main problems, students-experienced challenges, and solutions to offer based on the perspective of needs and difficulties. The researchers employed descriptive qualitative research. Meanwhile, the classroom action research approach was used in the first semester majoring in Tourism Travel at Politeknik Selaparang Lombok. Data collection was carried out by participatory observation, compiling instruments in the form of questionnaires of learning needs and difficulties, as well as focus group discussions (FGD) with two lecturers who have implemented English as the language of instruction with communicative delivery and three students majoring in Tourism Travel at Politeknik Selaparang Lombok taken by using purposive sampling technique. Results and discussion will be further discussed.